FACTORS AFFECTING THE EFFECTIVITY OF PROMULGATION AND IMPLEMENTATION STATE MANAGEMENT DECISIONS - Dao, Thuy Thi Thanh (Archives of Business Research, 2019)
State management reform is a regular and long-term activity for each country to improve the efficiency and competitiveness of the economy in order to adapt to the process of international economic integration. Vietnam as is an economy in the transition process, Vietnam is building actively an effective state management system. Making decisions in the state management on economy is one of the most effective tools to manage the economy. The paper explores the factors affecting the effectiveness of promulgation and implementation of decisions in state management on economy in the context of Vietnam’s transition economy. The paper builds a research model and surveys with 128 officials in state management agencies on economy and some experts. The research results identify the basic factors affecting the effectivity of promulgation and implemention decisions on economic management, propose some solutions to improve the effectivity of these decisions.